2020
DOI: 10.13057/biodiv/d210210
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetle assemblages in lowland forests of Pangandaran Nature Reserve, West Java, Indonesia

Abstract: Abstract. Priawandiputra W, Tsuji Y, Widayati KA, Suryobroto B. 2020. Dung beetle assemblages in lowland forests of Pangandaran Nature Reserve, West Java, Indonesia. Biodiversitas 21: 497-504. Dung beetles play crucial role in forest ecosystem, but no information on the dung beetle fauna has been reported in lowland forest of Java Island, Indonesia. Pangandaran Nature Reserve (PNR) area, which is recognized as lowland habitat of wildlife, can also support diversity of dung beetles. This study was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
0
11
1
1
Order By: Relevance
“…Kahono and Setiadi (2007) reported 28 species of dung beetle in mountain forest ecosystem of Pangrango National Park, West Java and the dominant species was Onthophagus variolaris Lansb (382 individuals). Priawandiputra et al (2020) also reported in the lowland forest ecosystem in the Pangandaran Nature Reserve, West Java and the dominant species was Onthophagus babirussa Eschscholtz (434 individuals). Dung beetles have also been reported in montane forest of the Harau Valley Nature Reserve, West Sumatra (Putri et al 2014); Kayan Mentaran National Park, East Kalimantan (Kahono & Ubaidillah 2003); Gunung Palung National Park, West Kalimantan (Malina et al 2018); and Lambusango Forest, Buton, Sulawesi (Moy et al 2016).…”
Section: Introductionmentioning
confidence: 66%
“…Kahono and Setiadi (2007) reported 28 species of dung beetle in mountain forest ecosystem of Pangrango National Park, West Java and the dominant species was Onthophagus variolaris Lansb (382 individuals). Priawandiputra et al (2020) also reported in the lowland forest ecosystem in the Pangandaran Nature Reserve, West Java and the dominant species was Onthophagus babirussa Eschscholtz (434 individuals). Dung beetles have also been reported in montane forest of the Harau Valley Nature Reserve, West Sumatra (Putri et al 2014); Kayan Mentaran National Park, East Kalimantan (Kahono & Ubaidillah 2003); Gunung Palung National Park, West Kalimantan (Malina et al 2018); and Lambusango Forest, Buton, Sulawesi (Moy et al 2016).…”
Section: Introductionmentioning
confidence: 66%
“…Laporan mengenai keanekaragaman hayati di kawasan ini antara lain primata, mamalia besar, dan vegetasi. Laporan keanekaragaman hayati serangga, seperti kumbang kotoran (dung beetle) di hutan Pangandaran juga sudah dilaporkan oleh Priawandiputra et al (2020), yaitu sebanyak 17 spesies dan Onthophagus babirussa (Eschscholtz) merupakan spesies dominan. Keanekaragaman kumbang cerambycid di kawasan hutan Pangandaran belum pernah di laporkan sebelumnya.…”
Section: Pendahuluanunclassified
“…Interestingly, surveys conducted in Singapore identified some species where wild‐caught males were consistently larger than females. Of particular interest is the species Onthophagus babirussa (Coleoptera: Scarabaeidae; Eschscholtz, 1822), which is widespread across Southeast Asia (SEA; Goh, 2014 ; Kudavidanage et al, 2012 ; Priawandiputra et al, 2020 ; Toh, 2019 ). Body size of specimens from Peninsular Malaysia appeared similar between the sexes, contrary to specimens collected from Singapore, despite relatively close proximity (~316 km).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, surveys conducted in Singapore identified some species where wild-caught males were consistently larger than females. Of particular interest is the species Onthophagus babirussa (Coleoptera: Scarabaeidae; Eschscholtz, 1822), which is widespread across Southeast Asia (SEA; Goh, 2014;Kudavidanage et al, 2012;Priawandiputra et al, 2020;Toh, 2019).…”
mentioning
confidence: 99%